Zika virus prevention behaviors and knowledge among male partners of pregnant people and lack of condom use as a prevention behavior from the Zika en Embarazadas y Niños (ZEN) prospective cohort study, Colombia - Christina L. Sancken; Ayzsa Tannis; Sandra A. Amouzou; Veronica Burkel; Jeffrey M. Carlson; Suzanne Newton; Suzanne M. Gilboa; Maritza Gonzalez; Diana Valencia; Van T. Tong; Martha Ospina (BMC Research Notes, 2024)
Abstract Objective Zika virus (ZIKV) infection in pregnancy can cause brain and eye abnormalities and neurodevelopmental sequelae. In the absence of medical countermeasures, behavioral interventions were recommended to prevent mosquito bites and sexual transmission of ZIKV. This report uses data from the Zika en Embarazadas y Niños (ZEN) prospective cohort study in Colombia to describe the knowledge, attitudes, and behaviors (KAB) related to ZIKV prevention in male partners compared to those of their pregnant partners at study enrollment during February 2017–2018. Results Most male partners reported wearing protective clothing such as long pants (97.6%) and long sleeves (72.8%), as well as covering ankles and feet (89.1%) to prevent ZIKV infection. When comparing the preventive behavior of condom use between male and pregnant partners, 26 pairs (10.0%) both responded that they performed the behavior. Overall, 25.1% of male partners and 18.9% of pregnant people reported any condom use during the three months before enrolling in ZEN. When comparing other preventive behaviors between male and pregnant partners, the behavior which was most frequently reported by both partners was wearing long pants (85.4%), and the least frequently reported by both partners was using condoms after finding out about a partner’s pregnancy (3.4%).